MENGOPTIMALKAN MANAJEMEN KONFLIK DALAM KEPEMIMPINAN KEPALA SEKOLAH MI - Moh. Ferdi Hasan; Shaleh (Study program PGSD FKIP Universitas Bung Hatta, 2023)
Conflict is an inevitable aspect in any organizational environment, including educational institutions. Effective conflict management is crucial for maintaining a harmonious and productive school environment. This research aims to identify effective strategies in optimizing conflict management in the leadership of MI school principals. The research method employed was a field study, involving direct observation and interviews with MI school principals who have successful experience in conflict management. Participants were selected based on their experience and reputation in conflict resolution. The results of this research reveal the presence of effective communication strategies, fair conflict resolution, and the development of an inclusive school culture as important factors in optimizing conflict management in the leadership of MI school principals. Principals who demonstrate the ability to listen empathetically, communicate clearly and openly, and build respectful relationships can create a harmonious school environment. Collaborative approaches, mediation, and emphasis on common interests contribute to fair conflict resolution. Additionally, building an inclusive school culture that encourages active participation from all stakeholders is essential. This research provides a significant contribution to our understanding of conflict management in the context of MI school principal leadership. The findings of this research can serve as a guide for MI school principals in addressing and resolving conflicts, as well as enhancing the quality of their leadership. Furthermore, this research provides a foundation for further studies in this field to develop more specific and effective strategies in optimizing conflict management in the leadership of MI school principals.